PENGARUH MANAJEMEN OPERASIONAL TERHADAP PENINGKATAN DISTRIBUSI PADA PT. XYZ (Studi pada PT. XYZ) - Leni Marlina; Adelina Suryati; Rili Septiefanera (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of Operational Management on Increasing Distribution at PT. XYZ. This research is motivated by the company's suboptimal distribution performance as shown by the achievement of On Time Delivery of 78.50% of the target of 95.00%, Order Accuracy Rate of 82.00% of the target of 100.00%, and the level of partner complaints of 12.00% of the maximum threshold of 5.00%. The study uses a quantitative method with a causal associative approach. The research population consists of all employees of PT. XYZ who are directly involved in operational and distribution activities are 100 people, with saturated sampling techniques so that the entire population is used as a sample. Data were collected through Likert 1–5 scale questionnaires, documentation, and literature studies. Data analysis was carried out through validity test, reliability test, classical assumption test, simple linear regression analysis, correlation coefficient, determination coefficient, and t-test using IBM SPSS Statistics version 27. The results of the study show that the research instruments are valid and reliable and the data meet the requirements of classical assumptions. Regression analysis yielded the equation Y = 2.421 + 0.920X. The results of the t-test showed a calculated t-value of 26.536 with a significance of 0.000 < 0.05, so that Operational Management had a positive and significant effect on Distribution Improvement. An R² value of 0.878 indicates that Operational Management explains 87.8% of the variation in Distribution Improvement, while 12.2% is influenced by other factors outside the research model.